Analisis Spasial Temporal Neraca Air DAS Kapuas, Kalimantan Barat Menggunakan Google Earth Engine dan Data Terraclimate: Spatial-Temporal Analysis of Water Balance in the Kapuas River Basin, West Kalimantan, Using Google Earth Engine and TerraClimate Data - Rifai, Mohamad (Jurnal Teknik Sumber Daya Air, 2025)
The Kapuas River Basin (DAS Kapuas) is the longest river system in Kalimantan. It plays a crucial role in water resource management, the sustainability of tropical rainforest ecosystems, and regional food security. In the face of climate change pressures, a deep understanding of water balance dynamics is key to effective water resource planning. This study presents a spatial-temporal analysis of the water balance in the Kapuas River Basin over the period 2014–2024, utilizing TerraClimate satellite data and the Google Earth Engine (GEE) cloud computing platform. The main variables such as precipitation, evapotranspiration, and runoff are integrated to calculate the water balance at a monthly scale. Results reveal strong seasonal patterns: average precipitation ranges from 150 to 400 mm/month, peaking between December and February, while evapotranspiration increases toward the end of the dry season (August–October). Runoff shows a high correlation with precipitation, particularly in steep upstream areas. Overall, the Kapuas River Basin is in a state of water surplus; however, significant reductions occurred during El Niño events (2015, 2019, and 2023), indicating vulnerability to climate anomalies. Spatial analysis reveals heterogeneous distribution: upstream and midstream regions exhibit high surplus (>100 mm/month), whereas downstream areas and degraded peatlands show low surplus or mild deficits. The integration of TerraClimate data and GEE proves effective for efficient, large-scale water balance monitoring and is highly replicable, offering a robust foundation for water resource management policies.